Who is the “public” when you make teaching public? Conceptions of audience in the scholarship of teaching and learning - Stanford T. Goto (Journal of the Scholarship of Teaching and Learning, 2009)
This article considers how SoTL practitioners have addressed three types of audiences: personal, administrative, and discipline-based. The analysis draws on narrative data from a collaborative SoTL project at a community college. The findings are discussed in relation to broader trends across institutions and disciplines. It is argued that investigators should take into account the audience’s epistemology of teaching. This approach helps investigators to enter into the professional discourse of that audience. Five strategies are offered to help SoTL practitioners communicate effectively with audiences outside of their professional area.